Clinical and Biological Markers in Hypereosinophilic Syndromes - Khoury, Paneez; Makiya, Michelle; Klion, Amy D. (Frontiers in Medicine, 2017)
Hypereosinophilic syndromes (HES) are rare, heterogeneous syndromes characterized by markedly elevated eosinophil counts in the blood and/or tissue and evidence of eosinophil-associated pathology. Although parasitic infections, drug hypersensitivity, and other disorders of defined etiology can present as HES (associated HES), treatment is directed at the underlying cause rather than the eosinophilia itself. A number of additional subtypes of HES have been described, based on clinical and laboratory features. These include (1) myeloid HES—a primary disorder of the myeloid lineage, (2) lymphocytic variant HES—eosinophilia driven by aberrant or clonal lymphocytes secreting eosinophil-promoting cytokines, (3) overlap HES—eosinophilia restricted to a single organ or organ system, (4) familial eosinophilia—a rare inherited form of HES, and (5) idiopathic HES. Since clinical manifestations, response to therapy, and prognosis all differ between HES subtypes, this review will focus on clinical and biological markers that serve as markers of disease activity in HES (excluding associated HES), including those that are likely to be useful only in specific clinical subtypes.